Brake control system for motorist vehicle - Muhamad Nor, Arif (2007)
Braking control system for motorist vehicle is a study and implements safety braking system into PLC (Omron) to control the speed of AC motor. The purpose of this project is to design and develop a brake control system using a Programmable Logic Control, (PLC) and implement it into brake control system nowadays. This brake system is using OMRON CQM1H programmable controllers as controller, MITSUBISHI FR-S 500 inverter as a converter to convert DC source from PLC to AC source for AC motor and DC voltage power supply as a sensor. This braking control system will detect any obstacle in front of the vehicle and reducing the AC motor rotation depends on the distance of the obstacle. This concept is almost similarly to nowadays braking control system, Adaptive Cruise Control (ACC). As a result, this brake control system is able to be controlled by varying the voltage regulated based on distance sensor specification. -Author